THE INFLUENCE OF PERCEPTION OF THE TEACHING PROFESSION ON THE INTEREST IN BECOMING A TEACHER: A CASE STUDY OF PROSPECTIVE TEACHERS - Meiriza, Mica Siar; Rahmadani Nasution, Putri; Muliani, Rizka; Hidayati, Sabilah; Nasution, Selviana (PROGRES PENDIDIKAN, 2025)
This study examines how teachers' perceptions influence individuals' interest in choosing a profession as a teacher. The aim is to uncover the impact of these perceptions on the interest in becoming a teacher, with the expectation that the findings will provide new insights for teacher recruitment strategies in the future and enhance the quality of education. The results are expected to offer recommendations for designing teacher professional development programs and serve as a reference for future researchers in exploring other factors influencing interest in becoming a teacher. The research type used is quantitative research with the dependent variable being the interest in becoming a teacher, and the independent variable being teachers' perceptions. The population in this study consists of students from the Economic Education Department, Faculty of Economics, Universitas Negeri Medan, class of 2021. The sample in this study is 70 students. Due to the relatively small population size, a saturated sampling technique was used. Data collection was conducted using a questionnaire, and data analysis was performed using simple regression. The findings of this study are expected to provide valuable insights into how teachers' perceptions impact students' career choices. By understanding these perceptions, education stakeholders can develop targeted strategies to improve teacher recruitment and retention. Moreover, the results could guide the creation of policies and programs aimed at improving the image of the teaching profession, thereby attracting more individuals to consider teaching as a viable and rewarding career. The study also has the potential to influence educational institutions and policymakers in designing more effective teacher professional development initiatives.